The Impact of Relationship Marketing on the Performance of Insurance Organisation - Epetimehin, Festus M. (Mediterranean Journal of Social Sciences, 2011)
Marketing is the life wire of any insurance. Insurance without a good marketing team and strategies is bound to fail. In orderto be relevant and be seen as being relevant to their customers, insurance have to innovate new strategies and install the art of technologythat will make life easy for customers and themselves. Customer Relationship Management Service is a marketing strategy that ensuresthe acquisition and retention of most profitable customers using the most effective method. The aim of this paper is to examine ifrelationship marketing practices as a new philosophy has been rightly adopted in the insurance industry. The study is based on theinformation gathered and collected from both primary and secondary sources. The sample for the study is made from selected insurancecompanies and their customers in Lagos Metropolis. Data analysis for the study was done using frequencies, percentage, and Z-score.Findings of the study revealed that relationship marketing practices have been playing a dominant role in improving the performance ofinsurance and increasing customers’ satisfaction through service quality. Therefore, the continued existence of any insurance will depend onits ability to maintain good relationship with customers and provision of quality service